Trichosporon asahii fungaemia in an immunocompetent polytrauma patient who received multiple antibiotics - Ding, Chuan Hun; Khaithir, Tzar Mohd Nizam; Wahab, Asrul Abdul; Faiz, Mohd Ali; Saarah, Wan Rosli (Malaysian Journal Pathology, 2024)
Indexed by WOS